Pengaruh Media Pembelajaran Prezi Terhadap Kemampuan Berpikir Kritis Peserta Didik Pada Mata Pelajaran IPS di Masa Pandemi - Nurasiah Jamil (PAKIS (Publikasi Berkala Pendidikan Ilmu Sosial), 2023)
Teachers require effective learning media to cultivate critical thinking skills in students, and Prezi is recognized as one such media. This study aims to explore the impact of utilizing Prezi as a learning medium on students' critical thinking skills in social studies at SMP Negeri 3 Bandung. A quantitative approach with a quasi-experimental method was employed for this research, utilizing a non-equivalent pre-test and post-test control design. The study involved two classes: Class VIII.2 as the experimental group and Class VIII.4 as the control group. The primary instrument used was a questionnaire on critical thinking skills, consisting of 34 items, distributed through Google Forms. The findings indicate that the use of Prezi as a learning medium in social studies significantly improved students' critical thinking abilities, with a significance value of 0.000, which is less than 0.05. In contrast, the control group, which utilized PowerPoint as the learning medium, showed a less significant impact on critical thinking skills, with a significance value of 0.002, greater than 0.05. When comparing the critical thinking abilities of students in both groups, there was no significant difference, as indicated by a significance value of 0.231, which exceeds 0.05.